A Study on Ecological Succession of Macrofouling Communities in Sea Cage Farm in South-West Coast of India: Life Sciences-Environment science for better human health - Mhaddolkar, Sonali S.; Dineshbabu, A.P.; Loka, Jayasree; Thomus, Sujitha (International Journal of Life Science and Pharma Research, 2021)
Development of aquaculture facilities like cages has led to rise in submerged structures which provide ample substratum to biofoulers which could greatly interfere with culture operations. An attempt was made to study the biofouling communities and succession of macro foulers on the cage culture net installed in the open sea. The main objective of the present study is to reveal the succession pattern of the biofouling communities on the panels of cage culture sites to find out seasonal settlement pattern, Dominant species and Climax community. A long-term study on the succession pattern of the cage farm experimental-net-panels revealed results as Hydroids-Gastropods-Hydroids-Barnacles-Modiolus-Green mussels. Hydroids were initial communities on the net panels and green mussels (Perna viridis) formed the climax community, also dominating on the cage culture nets. Different succession patterns were observed in two sites as well as in culture nets studied. The net panels of the cage were loaded with hydroids in the initial months and the peak fouling was during May. So frequent net cleaning was required during summer and during the spat settlement period of green mussel (September, October and November). Modiolus settlement during February month on the culture nets can be avoided by net exchange immediately after spat fall in this month. This attempt was made to study the ecological succession on the panels, in cages installed in Karwar, which is the first attempt, since the open sea cage culture was initiated in India. Looking at vast opportunities for further development in biofouling research, the aim of this investigations was to obtain the baseline information about the ecological succession pattern of biofouling organisms in fish cage sites. More research on biofouling in mariculture is essential to ensure the profitability of the aquaculture operations with environmental safety measures as a prime criteria